Evaluasi Pelaksanaan UNBK (Ujian Nasional Berbasis Komputer) (Studi Pada SMAN 5, SMKN 6 & SMK Wisnuwardhana Kota Malang) - Ernawan, Rizky Deandra (Jurnal Ilmiah Administrasi Publik, 2021)
The UNBK (Computer-Based National Examination) policy is one of the efforts to improve the implementation of national examinations at the elementary school to high school level. SMAN 5, SMKN 6 and SMK Wisnuwardhana are examples of schools that implement UNBK in the city of Malang. The implementation of the UNBK has been running from the 2015/2016 academic year to the 2018/2019 school year and the results can be evaluated. This study uses a qualitative method. For this reason, based on the CIPP implementation evaluation model taking into account the Context (Context), Input (Input), Process (Process), and Results (Product) factors, it can be said that the implementation of UTBK in the three schools is good, it's just that there is a decrease in student scores because the questions are tWoo difficult. and sometimes the question lattice doesn't come out. The factors that influence the implementation of UTBK are environmental culture; access to technology; and the condition of the socio-economic status of the community (students).